"NETWORKED INDIVIDUALISM" - A CHALLENGE OF DIGITALIZATION (Heritage, 2024)
The rise of digital technologies has transformed society into an entirely different environment for living and has turned the individual into an entity within which altered lifestyle habits are nurtured. The transformation of social relationships brought about by digitization is best illustrated through the concept of "networked individualism." The aim of this paper is to highlight the fundamental characteristics of this phenomenon, as well as its societal conditioning. The fundamental tenets of "networked individualism" manifest through two processes: the process of individualization and the process of societal incorporation of individualized individuals through networks. New technologies condition such a type of social relationships that is based on personal affinities. "Networked individualism" emerges as the dominant form of sociality resulting from the community's need, as a form of sociality, to establish itself as a network of interpersonal connections, providing a sense of belonging and social identity. On the one hand, this pointed to the impossibility of the community resisting the temptations of the digital era, and on the other hand, it showed its struggle to persist despite changing circumstances. Based on the consideration of various theoretical approaches, the authors observe that networked individualism is used as the primary analytical unit in understanding the organization of society. In this revised understanding, the individual is positioned as an autonomous center within communities characterized by weaker connections compared to their predecessors. The paper raises the question of how weaker connectivity affects social capital and its form in terms of Putnam's sense of bonding and bridging capital. The shift from dense to dispersed networks results in the transformation of membership from permanent to temporary, partial affiliations with different networks. Communication and interaction remain essential elements of everyday life but occur within the confines of loose networks. The consideration of this new type of social relationships through the so-called network analysis has opened the door to understanding the relationship between traditional and modern society, with a focus on their mutual interplay and complementarity.
Keywords: digitization, social relationships, networks, social capital,